Simplification Activities in a Network Scheduling Context - Abernathy, William J.; Demski, Joel S. (Management Science, 1973)
Network scheduling activities are usually addressed in a two-stage process of static schedule determination and subsequent control monitoring. A more complete view combines these two subsets of decisions with information acquisition decisions into a dynamic optimization framework. Such a framework is developed and the familiar static schedule-control process is then interpreted as a cost-effective simplification of the more complete dynamic formulation. This provides a framework for highlighting the numerous choices made in specifying the typical two-stage process and for evaluating the various choice alternatives. A simulation example illustrates the simplification and its evaluation with the more complete framework.